2015
DOI: 10.3390/ijms160511178
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Expansion of T Cells in Abdominal Aortic Aneurysm: A Role for Doxycycline as Drug of Choice?

Abstract: Most reported studies with animal models of abdominal aortic aneurysm (AAA) and several studies with patients have suggested that doxycycline favourably modifies AAA; however, a recent large long-term clinical trial found that doxycycline did not limit aneurysm growth. Thus, there is currently no convincing evidence that doxycycline reduces AAA expansion. Here, we critically review the available experimental and clinical information about the effects of doxycycline when used as a pharmacological treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…We have argued that the serum and tissue levels of tetracycline analogs obtained with standard medication will not be sufficient to affect MMPs. Instead, we think that the obtained results should be interpreted to be caused by inhibition of clonal cell proliferation [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have argued that the serum and tissue levels of tetracycline analogs obtained with standard medication will not be sufficient to affect MMPs. Instead, we think that the obtained results should be interpreted to be caused by inhibition of clonal cell proliferation [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of the three components of the trimolecular complex in AAA, and in particular the clonal expansions of the α- and β-chain TCR of T cells in AAA lesions ([10, 41], and this study), the association of AAA with MHC Class I and II [2022] and the identification of putative AAA antigens [2336], provide a compelling argument that AAA is a specific antigen-driven T-cell disease. AAA formation is controlled by cells, cytokines, and small molecules that inhibit inflammation (Table 1, [86]). Impaired immunoregulation may also play a role [3840].…”
Section: Discussionmentioning
confidence: 99%
“…Abdul-Hussien et al found 100 mg daily reduced AAA inflammation [25]. Recently, Kroom and Taanman [43] suggested doxycycline may inhibit clonal expansion of T-cells, and once a day dosing leads to troughs in doxycycline levels that reduce this effect. Unlike previous human AAA studies, we are measuring plasma doxycycline levels.…”
Section: Discussionmentioning
confidence: 99%